Imagining the body in tantric contemplative practice - Biernacki, Loriliai (International journal of Dharma Studies, 2017)
This paper addresses imagination, focusing on two words, bhāvana and vikalpa, both frequently translated as "imagination," and addresses the connections imagination has with the body, specifically within the context of contemplative practices. Drawing primarily from the 10th and 11th century philosophical school of the Pratyabhijñā of Abhinavagupta and Utpaladeva, this paper proposes a more complex understanding of imagination as consisting of different forms, some connected with the body, others not. This paper suggests that the medieval Indian understanding of imagination as linked to the body allows this term for imagination to side-step much of our current philosophical difficulty within contemporary coginitive science regarding the mind-body problem.